Integrating AI into Small Claims Courts: Lessons from Global Practices for Legal Reform in Indonesia - Satrio, Dwi Bintang; Artaji, Artaji; Fakhriah, Efa Laela; Yassine, Chami (Faculty of Law, Universitas Negeri Semarang, 2026)
Indonesia’s civil judicial system persists in facing procedural inefficiencies, especially with small claims, notwithstanding the implementation of the e-Court system. The lack of intelligent assistance in this digital infrastructure obstructs the achievement of efficient, rapid, and cost-effective adjudication as required by law. This study seeks to investigate the potential incorporation of artificial intelligence (AI) into Indonesia’s small claims process as a tool for legislative and institutional change. The research used a normative legal methodology, incorporating statutory and comparative analyses, to derive insights from the regulatory frameworks and judicial innovations of China, Singapore, and Canada. These jurisdictions have effectively utilized AI for claim classification, procedural assistance, and facilitating access for self-represented litigants, according to the results. In contrast to traditional digital technologies, AI facilitates cognitive capabilities like pattern identification and legal triage, which can substantially reduce administrative burdens and improve judicial uniformity. The study presents a reform approach for Indonesia that integrates AI in the initial procedural phases—specifically in claim registration and preliminary review—while maintaining judicial independence and due process. This study’s originality resides in its integration of comparative law, legal technology, and Indonesian procedural realities to present a contextually relevant, ethically informed paradigm for AI-enhanced adjudication. If properly regulated and strategically implemented, this integration can convert small claims courts into more accessible, efficient, and equitable institutions, reinforcing the judiciary’s constitutional responsibility in providing substantive justice.